Management of Cancer in the Digestive System - Liss Dyah Dewi Arini; Warsi Maryati; Puguh Ika Listyorini; Devi Pramita Sari (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Cancer is a non-communicable disease characterized by the presence of abnormal cells/tissues that are malignant, grow quickly and uncontrollably and can spread to other places in the patient's body. Cancer cells are malignant and can invade and damage the function of the tissue. Digestive cancer, also called gastrointestinal cancer, attacks the organs of the digestive system. Digestive cancer also includes gastrointestinal cancer, liver cancer, stomach cancer, colorectal cancer, and pancreatic cancer. Risk factors for digestive cancers are varied because many different organs can be affected. Some factors that contribute to cancer throughout the digestive system include age, heavy drinking (alcohol), smoking, and diabetes sufferers. This type of liver cancer is cancer that grows in liver cells. Liver cancer is a type of cancer that ranks second as the cancer that causes the most deaths in the world. Gastric cancer is a group of malignant diseases that have multifactorial causes, namely genetic, lifestyle and environmental factors. The symptoms caused by stomach cancer are initially not as typical as the symptoms of general digestive complaints. The diagnosis of colorectal cancer can be carried out in stages, including through an appropriate history, physical examination, and supporting examinations in the form of laboratory examinations, both from clinical laboratories and anatomical pathology laboratories. The etiology of colorectal cancer is currently still unknown. Symptoms of colorectal cancer are varied and non-specific. The main complaints of patients with colorectal cancer relate to the size and location of the tumor. Tumors in the right colon, where the contents of the colon are fluid, tend to remain hidden until they are very advanced.